Viral diversity in the European spruce bark beetle Ips typographus as revealed through high-throughput sequencing - Sutela, Suvi; Siitonen, Juha; Ylioja, Tiina; Vainio, Eeva J. (Elsevier, 2024)
The European spruce bark beetle, Ips typographus is the economically most important biotic damaging agent of Norway spruce. Efforts to delimit beetle populations by trapping, application of chemical insecticides, or mechanically excluding the beetles from their breeding substrates are often expensive and mostly inadequate. The use of natural enemies and viruses is receiving increased research interest as a potential environmentally healthy approach to control pest insect populations, but practical biocontrol methods against I. typographus are still lacking. To learn more about putative enemies of this pest species, we used high-throughput sequencing to determine its viral community using beetles collected at a Finnish forest site. The analysis revealed a diverse community of RNA viruses associated with I. typographus, including novel viruses that could be affiliated with the classified families Benyviridae, Metaviridae, Narnaviridae, Partitiviridae, Phenuiviridae, Solemoviridae, Virgaviridae, Tombusviridae, and proposed family Spiciviridae, as well as unclassified “quenyaviruses”. Based on phylogenetic analysis, the viruses were distinct from, but resembled, unclassified viruses originating from other arthropods, and many of them were distantly related to previously described viruses. The possibility that the viruses could be hosted by other organisms than the beetle itself (associated fungi, nematodes and protozoa) was addressed by bioinformatic and phylogenetic analyses and is discussed.
Keywords: norway spruce; pest insect; natural enemies; Riboviria; virome